ADAPTATION OF MODELS OF FOREIGN COUNTRIES IN THE MANAGEMENT OF MUNICIPAL DEVELOPMENT AND ITS RESOURCE PROVISION - Kokenova A.T.; Mashirova T.N.; Mamutova K.K.; Kaukeshova R.A.; Sabenova B.N. (Academic Journal of Physical and Chemical Sciences, 2020)
Sustainable development of territories, functioning of modern efficient economy, attraction of territorial potential for solving the most important range of strategic socially-oriented tasks of the state and local selfgovernment are based on the vital activities of institutional entities at various levels, including socio-ecological and economic complexes of municipalities. At present, there is a multi-level, multi-subject system of municipal resource management that is not able to provide solutions to the problems of sustainable development of the municipality and the necessary effectiveness of local government. In fact, there is a contradiction between the requirements of the market and the specifics of municipal management, which can be resolved on the basis of the formation and functioning of a system of resource support for sustainable development of the municipality. The resolution of this contradiction should be considered in the context of the institution of local self-government, its dual nature, expressed in a combination of state and social principles within this institution. This combination is determined by the need for citizens to participate in managing the Affairs of the country and the local community, and requires their own resources. Effective use of local resources is the main task, which will reduce the damage caused to the environment, improve the quality and standard of living of the population, the competitiveness and security of both municipalities, regions, and other economic agents. As a result of mastering the experience of the municipal governance structure in the West, this management system plays an important role in the free democracy of developed economies. The article analyzes the Western European theory and practice of complex solutions to issues of socioeconomic development of municipalities, including in the field of health and social security. An important task of municipalities is to maximize the potential of self-financing for the implementation of the developed strategy for the development of these entities, and to actively attract free funds of the population.